The Impact of Lumi Interactive on Students’ Achievement in Reading Comprehension - Lea Christina Br Ginting; Surya Setiadi Tarigan (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
This research aims to explore the effectiveness of teaching reading comprehension using two different learning media: Lumi Interactive and PowerPoint. This quantitative research approach focuses on comparing reading comprehension abilities between the experimental group and the control group. This study investigates whether students who teach using Lumi Interactive media show superior reading abilities compared to those using Powerpoint media. Data were analyzed using the Independent Sample T-Test. The results of data analysis from the experimental and control groups show the results of Sig. (2- tailed) 0.039 is lower than the alpha value of 0.05. It can be concluded that the null hypothesis (Ho) is rejected, which means the alternative hypothesis (Ha) is accepted. There is a significant difference in reading comprehension (reading perception) between students taught using interactive Lumi and those not using interactive Lumi. The average value of the experimental group was 82.00 while the average value of the control group was 77.90. Based on this analysis, it can be concluded that students in the experimental group showed higher skills than those in the control group, indicating that Lumi Interactive media in learning reading comprehension is effective.